The effect of miscellaneous oral dosage forms on the environmental pollution of sulfonamides in pig holdings. Issue 1 (December 2016) - Stahl, Jessica; Zessel, Katrin; Schulz, Jochen; Finke, Jan; Müller-Goymann, Christel; Kietzmann, Manfred
Abstract Background Due to antibiotic treatment of humans and animals, the prevalence of bacterial resistances increases worldwide. Especially in livestock farming, large quantities of faeces contaminated with antibiotics pose a risk of the carryover of the active ingredient to the environment. Accordingly, the aim of the present study was the evaluation of the benefit of different oral dosage forms (powder, pellets, granula) in pigs concerning the environmental pollution of sulfadiazine. Two subtherapeutic dosages were evaluated in powder mixtures to gain information about their potential to pollute the pig barn. Furthermore, a new group of pigs was kept in the stable after powder feeding of another pig group to determine the possible absorption of environmentally distributed antibiotics. Pigs were orally treated with three dosage forms. Simultaneously, sedimentation and airborne dust were collected and plasma and urine levels were determined. Results All formulations result in comparable plasma and urine levels, but massive differences in environmental pollution (powder > pellets, granula). Pigs housing in a contaminated barn exhibit traces of sulfadiazine in plasma and urine. Conclusion Using pharmaceutical formulations like pellets or granula, the environmental pollution of sulfonamides can significantly be diminished due to massive dust reduction during feeding.